Vaginal Metastasis from Colorectal Adenocarcinoma: Diagnosis in Cervicovaginal Cytology - Mendes, Marta Daniela Valente; Oliveira, Beatriz; Cunha, Celina; Coimbra, Nuno; Duarte, Anabela; Babo, Armanda; Martins, Conceição; Monteiro, Paula (Citotech Online - Case Review, 2016)
Metastatic colorectal adenocarcinoma in the vagina is rare and there are few reported cases in the literature. This paper reports a case of a woman with an infiltrative mass in the vagina and a previous diagnosis of colorectal adenocarcinoma. The use of cervicovaginal liquid based cytology together with CK20 and CDX2 immunostaining allowed to confirm the neoplasia’s colorectal origin. This case enhanced the importance of the clinical history as well as the immunohistochemical staining in a diagnosis, since without them and just with the cellular characteristics observed the diagnosis could be of endocervical or endometrial adenocarcinoma.